The role of the PRF in Oral and Maxillofacial Surgery - Martin Major; Bálint Trimmel; Melinda Polyák; Dávid Kovács; György Szabó (Hungarian Dental Association, 2022)
The method for the production of PRF (Platelet Rich Fibrin) was developed in 2000 and belongs to the second generation of platelet concentrates. Several clinical studies have demonstrated its effectiveness in combination with various bone substitutes. The concentrate is prepared by centrifuging the patient's own blood without addition of anticoagulants, and according to the established protocol. The process yields a fibrin-rich clot of leukocytes and platelets that serves as an extracellular matrix. The growth factors from white blood cells and platelets are released slowly (2-3 weeks), and thus, have a beneficial effect on the wound healing. In this article, the authors present their review of the data available in the main literature and report on potential applications of PRF in dental, dentoalveolar, and maxillofacial surgeries (implantology, bone grafting, dentoalveolar surgery, periodontology, sinus closure, sinus elevation, osteonecrosis, endodontics).